Ultrasound-guided local injection of methotrexate and systemic intramuscular methotrexate in the treatment of cesarean scar pregnancy - Young Ran Kim; Myoung Jin Moon (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveTo assess the efficacy and safety of ultrasound-guided intragestational injection of methotrexate (MTX) and systemic intramuscular MTX in the management of cesarean scar pregnancies.MethodsThis was a retrospective case-control study that included women diagnosed with cesarean scar pregnancy at CHA Bundang Medical Center unit between 2009 and 2015. The 26 cases were managed with local injection of MTX under ultrasound guidance and 15 cases were treated with systemic intramuscular of MTX. After the procedure, serial follow-up sonographic examination and serum beta-human chorionic gonadotropin (β-hCG) measurement were performed.ResultsThe mean initial β-hCG level was 20,610.73 mIU/mL and ranged from 263.00-71,316.50 mIU/mL. Mean gestational age was 6.3 weeks and ranged from 4.8 to 8.5 weeks. The majority of ectopic cases were treated successfully and follow-up β-hCG level declined abruptly following the first dose of MTX. The rate of success of local MTX treatment was significantly higher than that of systemic MTX treatment. It was 93.75% vs. 73.33%, respectively (P<0.05).ConclusionUltrasound-guided intragestational injection of MTX is an effective method for the management of cesarean scar pregnancies and is associated with minimal side effects and high treatment success.